2019
DOI: 10.4317/jced.55944
|View full text |Cite
|
Sign up to set email alerts
|

Oral neural tumors: Clinicopathologic analysis of 157 cases and review of the literature

Abstract: BackgroundOral neural tumors (ONTs) are rare lesions and represent reactive or neoplastic proliferations of nerve sheath cells. The purpose of the present study is to report the clinical, demographic and histopathologic features of 157 ONTs diagnosed in a single Oral Pathology Department and review the pertinent literature.Material and Methods157 cases of ONTs diagnosed during a 44-year period were retrospectively collected and the diagnosis was reconfirmed by studying representative haematoxylin and eosin sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 58 publications
0
24
0
4
Order By: Relevance
“…20 In this survey, as in the study by Alotaiby et al, 6 neurofibroma was the most frequent neural tumor. Conversely, Tamiolakis et al 39 reported granular cell tumor to be the most common neoplasm. Neural neoplasms can occasionally arise as intraosseous lesions.…”
Section: Discussionmentioning
confidence: 98%
“…20 In this survey, as in the study by Alotaiby et al, 6 neurofibroma was the most frequent neural tumor. Conversely, Tamiolakis et al 39 reported granular cell tumor to be the most common neoplasm. Neural neoplasms can occasionally arise as intraosseous lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Microscopicamente o TCG é pouco circunscrito e é constituído por células fusiformes, ovais com abundante citoplasma granular eosinofílico pálido e núcleo vesicular pequeno (Tamiolakis, Chrysomali, Sklavounou-Andrikopoulou, & Nikitakis, 2019). Usualmente as células são arranjadas em camadas, mas também podem ser encontradas em cordões e ninhos.…”
Section: Discussionunclassified
“…As células granulares parecem envolver ou substituir as fibras musculares (Tamiolakis et al, 2019). Além disso, a presença da hiperplasia pseudoepiteliomatosa que pode acometer 1/3 dos casos, pode induzir ao diagnóstico erróneo de carcinoma de células escamosas bem diferenciado (Alotaiby et al, 2019;Mendoza et al, 2020;Tamiolakis et al, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Because it has no tumor biological characteristics and structure, it is a non-genuine tumor, but it is easy to relapse after resection [18]. Solitary circumscribed neuromas (SCN), also known as Palisaded encapsulated neuroma (PEN), was rst reported in 1972 by Reed et al [19], The oral cavity is the second most frequent location for SCN after the skin, and it most often appears as painless super cial nodule same as MN [20].…”
Section: Introductionmentioning
confidence: 99%